The Republic of Belarus : First Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2011)
Belarus was experiencing an economic crisis after the expiration of a Stand-By Arrangement in March 2010. Its policies were loosened significantly, and consequently the account deficit increased and pressure on reserves intensified. The authorities agreed with the Eurasian Economic Community's Anti-Crisis Fund (ACF), which announced measures including tightening of macroeconomic policies and structural reforms. Executive Directors urged the authorities to restore external stability through further fiscal and monetary policy tightening. Directors stressed that the financial support will require demonstrated commitment to strong policies and structural reforms.